2019
DOI: 10.1590/1516-4446-2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of antidepressants in patients undergoing hemodialysis: a narrative literature review

Abstract: We conducted a narrative literature review on studies that specifically addressed the pharmacokinetics of antidepressants in patients on hemodialysis. The search included the MEDLINE, LILACS, and Web of Knowledge databases and combined Medical Subject Headings and free-text search terms for chronic kidney disease, end-stage renal disease, renal replacement therapy, depression, and antidepressants; it was limited to studies conducted in humans, with no language or time constraints. The search yielded 212 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Iwagami et al also found that antidepressant use in dialysis patients is one-and-a-half times higher than in the general population. Despite this, there are very few studies supporting the efficacy and the safety of antidepressant use in patients with CKD, and the evidence that does exist is generally gleaned from small non-randomized samples [ 168 ]. European Renal Best Practice 2014 guidelines recommends the first-line use of selective serotonin reuptake inhibitors (SSRIs) for up to 12 weeks in dialysis patients with moderate/major depression [ 169 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iwagami et al also found that antidepressant use in dialysis patients is one-and-a-half times higher than in the general population. Despite this, there are very few studies supporting the efficacy and the safety of antidepressant use in patients with CKD, and the evidence that does exist is generally gleaned from small non-randomized samples [ 168 ]. European Renal Best Practice 2014 guidelines recommends the first-line use of selective serotonin reuptake inhibitors (SSRIs) for up to 12 weeks in dialysis patients with moderate/major depression [ 169 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin reuptake inhibitors (e.g., citalopram, escitalopram, fluoxetine, paroxetine, sertraline) [139][140][141] Serotonin -norepinephrine reuptake inhibitors (e.g., Venlafaxine, duloxetine, mirtazapine) [139][140][141] Atypical antidepressants (e.g., bupropion, trazodone, nefazodone) [139][140][141] Tricyclic antidepressants (e.g., Amitriptyline) [139][140][141] Address contributing factors (e.g., pain, itching and mood disorders) Psychotherapy and cognitive behavioral therapy 131 24 Non-opioid analgesics (e.g., acetaminophen) and short acting non-steroidal anti-inflammatory drugs 23,24 For moderate pain, weak opioids (e.g., tramadol and oxycodone and hydromorphone) 23 For severe pain, higher doses of oxycodone and hydromorphone as well as long acting agents (e.g., fentanyl, buprenorphine or methadone) 24,25,28 Exercise, massage and physical therapy 27 Itching Gabapentin 100 mg daily along with continued assessment of symptom experience and titration by a medical provider [31][32][33] Difelikefalin at a dose of 0.5 mug per kilogram of body weight 36 Rehydrating emollients, aqueous gels, essential oils, topical capsaicin cream, gamma linolenic acid ointment, phototherapy and acupuncture 31,40 Nausea and vomiting For first line intervention for nausea, Ondansetron For second line intervention, metoclopramide 2.5 mg every 4 hours as needed if concern for gastroparesis or constipation. For third line intervention, olanzapine 2.5 mg every 8 hours as needed or haloperidol 0.5 mg every 8 hours as needed.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…Serotonin reuptake inhibitors (e.g., citalopram, escitalopram, fluoxetine, paroxetine, sertraline) [139][140][141] Serotonin -norepinephrine reuptake inhibitors (e.g., Venlafaxine, duloxetine, mirtazapine) [139][140][141] Atypical antidepressants (e.g., bupropion, trazodone, nefazodone) [139][140][141] Tricyclic antidepressants (e.g., Amitriptyline) [139][140][141] Address contributing factors (e.g., pain, itching and mood disorders) Psychotherapy and cognitive behavioral therapy 131 Exercise 132,133 Acupuncture 134 Magnesium 135 Chinese herbal medicine 136 Electroconvulsive therapy 137 Social support 138 Address concerns related to spirituality and religion 138 Relaxation techniques 138 J o u r n a l P r e -p r o o f…”
Section: Anxiety and Depressionmentioning
confidence: 99%
See 2 more Smart Citations